2009
DOI: 10.1086/597277
|View full text |Cite
|
Sign up to set email alerts
|

Tropheryma whippleiGlycosylation in the Pathophysiologic Profile of Whipple’s Disease

Abstract: T. whipplei glycosylation is likely to impair antibody-mediated immune recognition in patients. Such an intracellular antigen masking system in bacteria has not previously been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
2
27
0
1
Order By: Relevance
“…Paradoxically, the titer of specific immunoglobulin M (IgM) and IgG in classic Whipple's disease patients is very low or almost absent compared to carriers who do not show symptoms (87,88). This may be due to the bacterial antigen variation and/or masking from immunological detection, thereby allowing them to escape the humoral immune system (89). While IgM and IgG titers are low, the IgA titers in patients are usually much higher than in carriers (48).…”
Section: Pathogenesis Predisposing Factors For Classic Whipple's Diseasementioning
confidence: 99%
“…Paradoxically, the titer of specific immunoglobulin M (IgM) and IgG in classic Whipple's disease patients is very low or almost absent compared to carriers who do not show symptoms (87,88). This may be due to the bacterial antigen variation and/or masking from immunological detection, thereby allowing them to escape the humoral immune system (89). While IgM and IgG titers are low, the IgA titers in patients are usually much higher than in carriers (48).…”
Section: Pathogenesis Predisposing Factors For Classic Whipple's Diseasementioning
confidence: 99%
“…During our preliminary study, analysis of the signal intensity of GpTw110 after deglycosylation demonstrated a large, significant decrease in sera from patients but not from carriers [14]. These data were then used to establish a diagnostic test.…”
Section: Western Blot Interpretationmentioning
confidence: 87%
“…Moreover, there was a paradoxical association of Whipple disease with a lower immunological response in patients, compared with asymptomatic carriers [13]. An antigenic shift in the bacteria, most likely linked to the glycosylation process, resulted in this loss of specificity [14]. An enzyme-linked immunosorbent assay that targeted part of the hsp65 gene was not accurate or reliable for distinguishing patients from control subjects [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, secretory immunity may be also impaired, since Th1 cells play a crucial role in mucosal B-cell differentiation (9). In addition, T. whipplei acquires a glycoproteic biofilm that might inhibit the specific humoral immune response (1). Indeed, in serum samples of Whipple's disease patients, reduced total IgG2 (11) and T. whipplei-specific IgG and IgM have been detected, whereas T. whipplei-specific IgA is enhanced compared to healthy persons (2).…”
mentioning
confidence: 99%